1976
DOI: 10.1002/j.1537-2197.1976.tb13188.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Developmental Changes in Xanthium Induced by Gibberellic Acid

Abstract: One application of gibberellic acid (GA3) to Xanthium shoots resulted in an initial large stimulation, followed by inhibition, of internode elongation. After presumed translocation of the hormone from the locus of its application to the stem apex several morphological changes were observed. There was a significant increase in number of mitotic figures in the apical meristem and a twofold increase in volume of the apical dome. With time, the rate of leaf production was accelerated about 1.8 times. The phyllotax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In rosette plants, cell division is activated before stem elongation, and ·it is related to the action of gibberellins in the apical meristem (Sachs, 1965). Xanth£um treated with GA 3 showed a higher cell division rate, with doubling of AD size (Maksymowych et al, 1976). These results indicate that active cell division increases AD size during the vegetative stage.…”
Section: Discussionmentioning
confidence: 85%
“…In rosette plants, cell division is activated before stem elongation, and ·it is related to the action of gibberellins in the apical meristem (Sachs, 1965). Xanth£um treated with GA 3 showed a higher cell division rate, with doubling of AD size (Maksymowych et al, 1976). These results indicate that active cell division increases AD size during the vegetative stage.…”
Section: Discussionmentioning
confidence: 85%
“…Because the phyllotaxy of pla1 is normal, positional regulation of leaf primordia is not affected, suggesting that in pla1, enlarged SAM is differently organized from that of abphyl. It was reported that exogenous application of a gibberellic acid resulted in the enlargement of SAM via activated cell divisions, and that rapid leaf initiation and phyllotactic change in Xanthium pennsylvanicum (49)(50)(51). Also, the inhibition of auxin transport affects the phyllotaxy and leaf emergence rate in Arabidopsis and tomato (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments provided evidence that factors of either a chemical or a physical nature could affect leaf position and the angle between leaves. Not surprisingly, the classical plant hormones, particularly auxin and gibberellin, were implicated, although their specific role in organ initiation and positioning has not been determined (Snow and Snow, 1937;Gorter, 1949Gorter, , 1951Bedesem, 1958;Kiermayer, 1960;Schwabe, 1971;Maksymowych and Maksymowych, 1973;Maksymowych et al, 1976;Maksymowych and Erickson, 1977;Meicenheimer, 1981).…”
Section: Introductionmentioning
confidence: 99%